THE PROBLEM OF TOLERANCE IN ORIENTAL PHILOSOPHY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article briefly discusses some of the views of Eastern thinkers on tolerance and dogmatism.